Distribution and prevalence of Borrelia burgdorferi sensu lato in Ixodes ricinus ticks of canton Ticino (Switzerland) - Jouda, Fatima; Crippa, Mara; Perret, Jean-Luc; Gern, Lise (My University, 2003)
Free-living Ixodes ricinus ticks were collected from 12 different sites of canton Ticino, south of the Alps (Switzerland). Each tick was examined for the presence of Borrelia burgdorferi sensu lato (sl), the etiologic agent of Lyme borreliosis using direct fluorescent antibody assay, and isolation of the bacteria. Borreliae were characterized by PCR followed by RFLP. The abundance and infection rates of I. ricinus ticks varied greatly between the areas. Two localities were found free of Borrelia. The prevalence of infected ticks ranged from 5 to 19%. Most ticks (96%) were found infected by <50 spirochetes. Three B. burgdorferi sl species were successfully isolated: B. garinii dominated, followed by B. lusitaniae and B. valaisiana. Additionally, a mixed infection with B. garinii and B. valaisiana was observed. The distribution of the various Borrelia species in the different areas was heterogeneous. This is the first report of the presence of B. lusitaniae in I. ricinus in Switzerland.
Keywords: Borrelia burgdorferi sensu lato; Borrelia lusitaniae; Ixodes ricinus; Switzerland